(untitled) (Annals of Medicine and Medical Sciences, 2025)
Background: Focal thyroid incidentalomas (FTIs) found on 18F-FDG PET/CT (Fluorine-18-Fluorodeoxyglucose Positoin Emission Tomography/Computed Tomography) examinations are becoming commonplace in routine clinical practice. While in most situations benign, a high percentage.Objective and Aims: Establish the pooled prevalence and risk of malignancy of FTIs on PET/CT and define imaging and clinical risk markers of malignancy. Research questions: What is the malignant rate of FTIs recognized with 18F-FDG PET/CT, and what risk stratification factors are?Methods: PubMed, Scopus, and Web of Science were searched extensively to compile studies between 2015 and 2025. Included were studies that reported sample size and results in relation to malignancy. Data extraction and quality assessment were carried out with the Newcastle-Ottawa Scale. Random-effects meta-analysis was applied to establish pooled prevalence and 95% confidence intervals.Results: Ten studies with 2,500 patients were reviewed. The combined prevalence of FTIs was 2.5%, with an overall risk of malignancy of 30%. Elevated SUVmax (standardized uptake value), suspicious ultrasound morphology, and cytologic proof were reliable predictors of malignancy.Conclusion: FTIs on PET/CT carry high malignancy risk, necessitating systematic evaluation with combined metabolic, morphologic, and cytologic analysis. Reporting and risk stratification guidelines should be established. Prospective research should focus on development of AI-based predictive models and machine learning algorithms to enhance early detection and reduce unnecessary procedures.